2018
DOI: 10.1007/s00345-018-2184-z
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy-free ultrasonography-guided percutaneous nephrolithotomy in pediatric patients: a single-center experience

Abstract: The results of this study showed that fluoroscopic-free ultrasound-guided PCNL in pediatric patients of all ages is safe, highly efficient, and minimizes potential radiation exposure risks associated with the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Ultrasound-guided PCNL without uoroscopy has advantages and disadvantages. Advantages are avoidance of X-ray exposure especially in children 17,20 or pregnant women, no need for lead shielding, possible avoidance of intraabdominal organs in the access path, and possible avoidance of renal vessels using Doppler ultrasound. Nevertheless, it has some disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided PCNL without uoroscopy has advantages and disadvantages. Advantages are avoidance of X-ray exposure especially in children 17,20 or pregnant women, no need for lead shielding, possible avoidance of intraabdominal organs in the access path, and possible avoidance of renal vessels using Doppler ultrasound. Nevertheless, it has some disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Most PCNL procedures are performed under fluoroscopic guidance. However, a previous study demonstrated that ultrasound-guided PCNL reduces cost and radiation exposure and even has the same effect in some special cases, such as pediatric patients with calculi 23 and patients with a retrorenal colon. 24 Only ultrasound has been used in all three dilation procedures in our urology operating room.…”
Section: Discussionmentioning
confidence: 99%
“…However, as success rates have increased and particular experience has been gained in adults, the technique has also begun to be performed in children as monotherapy, or in combination with other approaches in patients with large stone burdens. Concerns about long-term renal damage, small kidney size, relatively big tools, radiation exposure, and danger of significant problems, such as hemorrhage, contributed to the technique's slow adoption in children [ 48 , 49 ].…”
Section: Pnlmentioning
confidence: 99%